JOMBACAPERLIS@Grab - Bakhtiar, Haizatul Afni; Ali, Mohd Azman; Hashim, Zairina; Ismail, Mohd Bukhari (Universiti Teknologi MARA, Kedah, 2018)
Perlis State Public Library is committed in providing reading materials to the people of Perlis with the mission of providing information resources that can be used by all societies to enhance knowledge and to create a culture of reading and knowledgeable society. In order to achieve the mission, Perlis State Public Library has taken the initiative by cooperating with Grab Perlis driver in cultivating the people in the state to read and promote lifelong learning through the services of JOMBACAPERLIS@Grab. Grab is selected as it is the latest service trend that has been in great demand among public service users. Malaysians choose to use this service as it is convenient, cheap, comfortable and fast. It is an effort to encourage Grab users to read and user can fill the time in the vehicle by reading. The program has received Grab Perlis cooperation with the involvement of 20 Grab vehicles in Perlis at the start. The program was launched by YB Dato' Dr. Syed Omar Sharifuddin bin Syed Ikhsan, Perlis State Secretary on April 24th, 2018 in conjunction with the Let's Read Together program for 10 minutes at the Perlis State Public Library. In this program Perlis State Public Library has provided reading materials for Grab Car to be used by Grab users to read throughout their journey to the destination. Although the duration of the trip is short, their time will hopefully be filled with upgrading their knowledge. Novelty and uniqueness: JOMBACAPERLIS@Grab was first introduced in Malaysia to promote reading among community using e-hailing services which is Grab car.